An immunohistochemical study on the endocrine cells in the gastrointestinal tract of the freshwater turtle, Mauremys caspica caspica - Tarakçi, BG; Köprücü, SS; Yaman, M (Tubitak Scientific & Technological Research Council Turkey, 2005)
The regional distribution of endocrine cells was studied in the gastrointestinal tract of the freshwater turtle, Mauremys caspica caspica, by immunohistochemistry using antisera against serotonin, somatostatin, gastrin, insulin, substance P, glucagon and calcitonin gene related peptide (CGRP). The immunoreactive cells were located in the gastric glands of stomach regions and in the intestinal epithelium with variable frequencies. Most of the immunoreactive cells in the intestine were spherical or spindle-like in shape (open-type cells), while round cells (closed-type cells) were occasionally found in the stomach. Serotonin-immunoreactive cells were most commonly found in the pylorus and duodenum. Gastrin-immunoreactive cells were restricted to the ileum and rectum at low frequencies. Insulin-immunoreactive cells were detected from pyloric to rectum. No substance P, glucagon, somatostatin or CGRP-immunoreactive cells were found in this study.
Keywords: Mauremys caspica caspica; immunohistochemistry; stomach; intestine; endocrine cells